Practical Considerations & Good Protocol for the Interpretation of Ultramafic & Mafic Rock Physical Property Data. Issue 1 (1st December 2018) - Adams, Cameron; Dentith, Michael
Abstract : An increase in the availability of inexpensive and easy-to-use geophysical tools has led to an interest in the development of larger rock physical databases. These data are often interpreted at face value, with little consideration given to the selection of representative samples, sample preparation, or even the practical limitations of measuring tool. Consequently, wide-ranging data are often observed. This may lead to incorrect interpretation. Magnetic susceptibility and density measurements are now routinely made on drill-core specimens. These data are often amalgamated with historical measurements in an effort to make localised physical property databases more robust. Two practical considerations regarding these data are discussed: 1) The evaluation of dry bulk density data, and inherent issues with measuring dimensions or applying volume assumptions; 2) The appropriateness of using commonly employed inductive electromagnetic tools, i.e. handheld magnetic susceptibility meters, to resolve induced magnetisation. Changes in core-diameter due to coring and rock swelling are studied, as are the effects of core volume loss due to cutting. A comparison between empirical measurements and volume estimations has shown that up to 7% and 30% of variability may be attributed to changes in drill-core diameter and split-core geometry, respectively. Dry bulk density data that have been calculated using estimated volumes may be in extreme error and therefore inappropriate to use. Orientation markings or bottom-of-hole lines have shown to correlate with reduction in variability of core volume loss caused by cutting. The use of an Almonte core-holder, or similar, is shown to produce an even lower and less variable core volume loss. The reliability of historical dry bulk density values may be ranked based on the presence of orientation or bottom-of-hole line, or known implementation of a core cutting holders. Bulk magnetic susceptibility measurements made on ultramafic and mafic diamond drill-core using a handheld instrument are evaluated. Comparisons with Qmeter magnetisation data show that handheld bulk magnetic susceptibility values may be in the error of several orders of magnitude. Anisotropy is hypothesised to be the principal cause of variation. Furthermore, conductivity effects that are induced by handheld meters, e.g. frequency dependence, may contribute to an under-reporting of values.